2003
DOI: 10.1128/jvi.77.7.4401-4408.2003
|View full text |Cite
|
Sign up to set email alerts
|

Cytoskeletal Requirements for Hepatitis C Virus (HCV) RNA Synthesis in the HCV Replicon Cell Culture System

Abstract: Hepatitis C virus (HCV) induces microtubule aggregates in infected hepatocytes. To determine if cytoskeletal elements are important for HCV RNA synthesis, we examined the effect of cytoskeleton inhibitors on HCV replicon transcription in Huh7 cells. The data demonstrate that HCV replication complex-mediated RNA synthesis requires microtubule and actin polymerization.Hepatitis C virus (HCV) infection is the leading cause of liver transplantation in the United States, with sequelae including liver fibrosis, cirr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

10
52
1

Year Published

2009
2009
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 71 publications
(63 citation statements)
references
References 37 publications
10
52
1
Order By: Relevance
“…7d). Contrary to our studies, other studies have found that nocodazole treatment inhibits microtubule-dependent transport of the HCV replication complex, initiation of productive HCV infection, and, as a result, HCV RNA replication (75,77,78). Moreover, two recent reports have shown that postassembly the vesicular HCV core protein puncta traffic via microtubules and that trafficking is inhibited by nocodazole treatment (28,50).…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…7d). Contrary to our studies, other studies have found that nocodazole treatment inhibits microtubule-dependent transport of the HCV replication complex, initiation of productive HCV infection, and, as a result, HCV RNA replication (75,77,78). Moreover, two recent reports have shown that postassembly the vesicular HCV core protein puncta traffic via microtubules and that trafficking is inhibited by nocodazole treatment (28,50).…”
Section: Discussioncontrasting
confidence: 99%
“…Thus, we determined the roles of actin and/or microtubule cytoskeletons in CCCM HCV infection. The actin cytoskeleton has been shown to be involved in interaction with multiple steps of cell-free HCV infection, including viral entry (44,74) and replication (75,76). In agreement with these findings, our studies have shown that an intact actin network was required for CCCM HCV transfer, as treatment with actin polymerization inhibitor cytochalasin D in the coculturing assay prevented CCCM HCV transfer ( Fig.…”
Section: Discussionsupporting
confidence: 88%
“…Once present, ANXA2 participates in the formation of higher-order structures of the membranous web via its membrane organization functions (67), possibly stabilizing membrane microdomains involved in virion morphogenesis. Alternatively, it also could provide contacts to the actin cytoskeleton (23,48), which has been shown to be linked to HCV replication complexes (10,28). Interestingly, ANXA2 has been identified in a pulldown of NS3 from HEK 293T cells expressing NS3/4A together with components of the cytoskeleton, providing some evidence for this concept (28).…”
Section: Discussionmentioning
confidence: 99%
“…However, this does not mean that F protein has no correlation with HCV replication. It was reported that HCV replication complex-mediated RNA synthesis requires intact microtubule and actin polymerization (28). Therefore, interruption of normal microtubule formation likely results in decreased HCV replication.…”
Section: Discussionmentioning
confidence: 99%